PARP Inhibitors in the Treatment of Ovarian Cancer: a review of the latest research - Zuzak, Andrzej Paweł; Satora, Małgorzata; Cieślik-Porębska, Magdalena; Kułak, Krzysztof; Niewiadomska , Jagoda (Journal of Education, Health and Sport, 2025)
Introduction Ovarian cancer is a leading cause of cancer mortality globally due to late-stage diagnosis and limited treatment options. PARP inhibitors have shown promise as effective treatments for recurrent and various stages of ovarian cancer. Aim of the Study This study reviews the efficacy and application of PARP inhibitors in ovarian cancer treatment over the past 15 years, focusing on literature from the PubMed database post-2009 and considering FDA and EMA guidelines. Review methods A literature review was conducted using the PubMed database, focusing on studies published after 2009. The review also incorporated recommendations from the FDA and the European Medicines Agency regarding the use of PARP inhibitors in ovarian cancer treatment. Results The findings highlight the substantial impact of PARP inhibitors on ovarian cancer treatment, improving PFS and overall outcomes. Olaparib, niraparib, and rucaparib have become integral to ovarian cancer management, offering effective options for patients with BRCA mutations or homologous recombination deficiencies. These inhibitors have been validated in multiple clinical trials, underscoring their robustness and effectiveness. Combination therapies, such as olaparib with bevacizumab, further enhance therapeutic outcomes, showcasing the potential for synergistic effects. Summary PARP inhibitors represent a significant advancement in ovarian cancer treatment, offering improved survival outcomes for patients with specific genetic profiles. Their integration into standard care protocols underscores their importance and efficacy, providing valuable therapeutic options in the fight against ovarian cancer.